Identitas Budaya pada Pemain Game Online ”Sky Children of the Light”: Pendekatan Etnografi Virtual - Narasrey Merinda; Zainal Abidin; Maulana Rifai (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Online Game: Sky Children of The Light is an adventure game that allows each player to meet others with different cultural backgrounds and languages without the need to enter a specific server. This game is developed by the company ThatGameCompany. The objective of this research is to understand how "Cultural Identity in the Interaction of Players in the Online Game Sky Children of The Light." This research uses a qualitative method and a virtual ethnography approach. The research process involves techniques such as interviews, observations, and the analysis of necessary data. The theoretical foundation for this research is the social identity theory by Henri Tajfel. The results of this research show that cultural identity in the game Sky is highly diverse due to players with various cultural backgrounds. These differences often lead to intercultural conflicts within the game.